2004
DOI: 10.1073/pnas.0307288101
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of antagonists of growth hormone-releasing hormone substituted at positions 8, 9, and 10

Abstract: Antagonists of human growth hormone-releasing hormone (hGHRH) with increased potency and improved enzymatic and chemical stability are needed for potential clinical applications. We synthesized 21 antagonistic analogs of hGHRH(1-29)NH2, substituted at positions 8, 9, and 10 of the common core sequence {phenylacetyl-Tyr 1 , D-Arg 2,28 , para-chloro-phenylalanine 6, Arg 9 ͞homoarginine 9, Tyr 10 ͞O-methyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…In recent years several series of antagonistic analogs of growth hormone-releasing hormone (GHRH) were synthesized in an endeavour to develop a new class of antineoplastic agents [8][9][10][11]. GHRH antagonists inhibit the growth of various experimental human cancers [12], but their effects on triple-negative breast cancers have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years several series of antagonistic analogs of growth hormone-releasing hormone (GHRH) were synthesized in an endeavour to develop a new class of antineoplastic agents [8][9][10][11]. GHRH antagonists inhibit the growth of various experimental human cancers [12], but their effects on triple-negative breast cancers have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that GHRH antagonists can inhibit the proliferation of diverse cancer lines by direct action in vitro, under conditions in which the contribution of the hypothalamic GHRH/pituitary GH/hepatic IGF-I axis is clearly excluded [8,[13][14][15][16][17][18][19][20][21][22][23][24][25]. These studies led to the conclusion that the main mechanism responsible for tumor inhibition could be a direct effect of the antagonists on the tumor tissue [8,11]. These findings may now be explained by recent discoveries regarding the role of tumoral GHRH and GHRH receptors in the proliferation of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…SV-1 differs from the pituitary GHRH-R in a small portion of its amino-terminal region. Many antagonistic analogs of GHRH have been synthesized (2,5,7,8). These analogs inhibit tumor growth by blocking GH and hepatic secretion of insulinlike growth factor 1 (IGF-1), as well as by suppressing the synthesis of tumoral autocrine/paracrine IGF-1 and/or IGF-II (8)(9)(10)(11), and by blocking the effects of autocrine GHRH on tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH)-releasing hormone (GHRH) is a 40-44 amino acid hypothalamic peptide that regulates the secretion of GH from the anterior pituitary gland (5). In addition to having neuroendocrine action, GHRH acts directly on a variety of peripheral tissues and tumors and induces cell proliferation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GHRH antagonists can suppress tumor growth indirectly by blocking GH release from the pituitary and consequently the hepatic production of IGF-I (6,12), which is an established mitogen for various cancers (13), is likewise inhibited. Nevertheless, GHRH antagonists, exert their main antitumor effects through direct mechanisms (12,14), by the inhibition of tumoral GHRH and IGF-I and/or IGF-II (6,(14)(15)(16), which serve as autocrine/paracrine growth factors. Pituitary-type GHRH receptors (pGHRH-R) and their splice variants (SVs) have been detected in different human cancers and various cancer cell lines (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%